A Centralized E-Health Medical Records Security Using aes Technology - Mohammed, Moulana; Sowjanya, Atmakuri (Journal of Neonatal Surgery, 2025)
In this research work an adaptive centralized E-health management system and its security are initialized using MySQL based PowerBi platform. Medical records monitoring as well as its security has been important to future generations. The centralized storage system is playing a key role in this contest, moreover proposed model has been implemented using AES technology. Medical records sharing is very important for clients, users, doctors and third parties but when sharing documents there may be a chance to get hack significant information. In this study using AES algorithm has been providing security to medical records using encryption and decryption (via key). The centralized dashboard, nothing but patients and doctor’s dashboard is maintained by designed application using MySQL based PowerBi tool. This application provides performance measures in terms of accuracy 98.34%, sensitivity 94.35%, recall 93.23%, encryption rate 76.34% and decryption rate 75.34& had been attained which have been outperforming the methodology and compete with present technology